Barbados. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Barbados during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as aquaculture, apiculture, sheep farming, agrotourism, food security and safety, sustainable agriculture and laboratory management. Likewise, work was done on financing and improving the infrastructure of the Livestock Research Station in Greenland. Finally, support was given to young agribusinesses, as well as a presentation on food fraud and social networks were used as a means to provide communications.